POLITIK HUKUM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - sodikun sodikun (MIH Unsoed, 2021)
Legal politics determines the direction of legal development, if the direction of legal development is laid on a solid foundation and foundation, then the law will provide protection for people's lives. The policy of developing national law is in line with the ideals of the proclamation of the Indonesian nation, to achieve a just and prosperous Indonesia. The preparation of regional budgets has a very important meaning in the same goal of achieving a prosperous society.Legal politics is directed towards the creation of regional revenue and expenditure budgets in accordance with laws and regulations, implementation of the vision, mission and development programs of regional governments, both the Regional Development Work Plan (RKPD), the Regional Medium-Term Development Plan (RPJMD), and the Regional Long-Term Development Plan (RPJMD). RPJPD).The Regional Revenue and Expenditure Budget (APBD) is the basis for regional financial management within 1 (one) fiscal year. The Regional Head is required to prepare a General Budget Policy (KUA)/Priority and Temporary Budget Ceiling (PPAS) based on the Regional Development Work Plan (RKPD). The KUA PPAS, which has been agreed by the regional head with the DPRD, becomes the guideline for regional apparatuses in preparing work plans and budgets for regional apparatus work units. The work plan and budget of the SKPD are submitted to the Regional Financial Management Officer (PPKD) as material for the preparation of the draft Perda APBD for the following year. The process of preparing the Regional Revenue and Expenditure Budget (APBD) begins with the preparation of the draft General Budget Policy (KUA) as well as the Priority and Temporary Budget Ceiling (PPAS) document. Then the two documents were discussed with the DPRD to produce a Memorandum of Understanding between KUA and PPA. Based on the Memorandum of Understanding, the Regional Head submits a circular containing the Guidelines for the Preparation of the RKA-SKPD followed up by the SKPD-SKPD by preparing the RKA SKPD. Furthermore, the Regional Financial Management Officer (PPKD) compiles the RKA SKPD into a Raperda APBD to be discussed and obtain joint approval with the DPRD before being submitted to the evaluation process.